Degradation alters the lubrication of articular cartilage by high viscosity, hyaluronic acid‐based lubricants. Issue 5 (5th December 2017) - Bonnevie, Edward D.; Galesso, Devis; Secchieri, Cynthia; Bonassar, Lawrence J.
ABSTRACT: Hyaluronic acid (HA) is widely injected as a viscosupplement in the treatment of osteoarthritis. Despite its extensive use, it is not currently known if cartilage degradation alters how HA‐based solutions lubricate the articular surface. In this study we utilized a model of cartilage degradation by IL‐1β along with a recently developed framework to study role of cartilage degradation on lubrication by clinically‐approved HA‐based lubricants with high viscosities. Cartilage explants were cultured up to 8 days with 10 ng/ml IL‐1β. After culture, samples were examined histologically, immunohistochemically, biochemically, mechanically, topographically, and tribologically. The tribological testing analyzed both boundary and mixed lubrication modes to assess individual effects of viscosity and boundary lubricating ability. Friction testing was carried out using PBS and two clinically approved HA‐based viscosupplements in a cartilage‐glass configuration. After culture with IL‐1β, boundary mode friction was elevated after both 4 and 8 days. Additionally, friction in mixed mode lubrication, where HA is most effective as a lubricant, was significantly elevated after 8 days of culture. As cartilage became rougher, softer, and more permeable after culture, the boundary mode plateau was extended, and as a result, significantly increased lubricant viscosities or sliding speeds were necessary to achieve effective mixed lubrication. Overall, this study revealed that lubrication of cartilage by HA is degradation‐dependent and coincides with changes in mechanics and roughness. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1456–1464, 2018.